2006
DOI: 10.1159/000091456
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Stimulates Activity and Surface Expression of NHE3 in Human Primary Proximal Tubule Epithelial Cells (RPTEC)

Abstract: The steroid hormone aldosterone is a major regulator of extracellular volume and blood pressure. Aldosterone effectors are for example the epithelial Na+ channel (ENaC), the Na+-K+-ATPase and the proximal tubule Na+/H+ exchanger isoform 3 (NHE3). The aim of this study was to investigate whether aldosterone acts directly on proximal tubule cells to stimulate NHE3 and if so whether the EGF-receptor (EGFR) is involved. For this purpose, primary human renal proximal tubule cells were exposed to aldosterone. NHE3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 31 publications
2
43
0
1
Order By: Relevance
“…Whether this regulation occurs in native proximal tubules is unknown; however, cAMP and Ca 2ϩ are important regulators of ion transport and the absorptive functions of proximal tubule segments. Aldosterone has been shown recently to increase the apical abundance and activity of NHE3 in proximal tubules of adrenalectomized rats in vivo and in a human proximal tubule cell line 72,73 ; however, these effects are long term (3 to 5 days), and the possible role of nongenomic mechanisms was not reported. Nevertheless, when combined with the additional observations that NHE3 is regulated via a nongenomic pathway by glucocorticoids in a proximal tubule-derived cell line (OKP) 36 and that NHE3 is a target for nongenomic regulation by aldosterone in the MTAL, 20 there exists a strong basis for the hypothesis that aldosterone may influence proximal Na ϩ and fluid absorption through nongenomic regulation of NHE3.…”
Section: Proximal Tubulementioning
confidence: 97%
“…Whether this regulation occurs in native proximal tubules is unknown; however, cAMP and Ca 2ϩ are important regulators of ion transport and the absorptive functions of proximal tubule segments. Aldosterone has been shown recently to increase the apical abundance and activity of NHE3 in proximal tubules of adrenalectomized rats in vivo and in a human proximal tubule cell line 72,73 ; however, these effects are long term (3 to 5 days), and the possible role of nongenomic mechanisms was not reported. Nevertheless, when combined with the additional observations that NHE3 is regulated via a nongenomic pathway by glucocorticoids in a proximal tubule-derived cell line (OKP) 36 and that NHE3 is a target for nongenomic regulation by aldosterone in the MTAL, 20 there exists a strong basis for the hypothesis that aldosterone may influence proximal Na ϩ and fluid absorption through nongenomic regulation of NHE3.…”
Section: Proximal Tubulementioning
confidence: 97%
“…NHE3 is the main transporter facilitating Na + reabsorption in the proximal tubule, where >60% of the NaCl conservation by the nephron occurs. NHE3 activity in human primary renal proximal tubule epithelial cells (RPTECs) was sensitive to aldosterone treatment over 72 h (106). However, MR is expressed only at very low levels in the proximal tubule, whereas GR is at much higher abundance (19).…”
Section: + /H + Exchanger Regulation By Rapid Aldosterone Signalingmentioning
confidence: 99%
“…Importantly, the EGFR cascade is also linked to other important signaling components of aldosterone like G protein-coupled AT1 and GPER signaling and PDGFR activation. Physiological MR effects mediated via EGFR include processes that enhance surface expression of different transporters like ENaC (McEneaney et al 2007), NHE1 (Gekle et al 2002) or NHE3 (Drumm et al 2006) in epithelial tissues. Pathophysiological MR actions mediated by EGFR include proinflammatory effects in vessels, where aldosterone can increase lipoxygenase expression via MAPK activation (Limor et al 2009) and where enhanced TGFbeta, ICAM1 and collagen I expression in VSMCs of aged rats can be attenuated by MR or MAP kinase inhibitors (Krug et al 2010).…”
Section: Egfrmentioning
confidence: 99%
“…Although the effect is persistent and lasting over several days, the involvement of the EGFR signaling pathways indicates a possible nongenomic mechanism (Krug et al 2003, Drumm et al 2006. Furthermore, it has been demonstrated that NHE3 expression is increased via SGK1 and genomic effects on the long-term (Musch et al 2008).…”
Section: :1mentioning
confidence: 99%